Tingkat Kepuasan Konsumen Terhadap Pelayanan Kefarmasian di Apotek Armada Kabupaten Wonogiri - Geffi Audystivirani, Keysha; Mursiany, Anita (Jurnal Farmasi (Journal of Pharmacy), 2025)
Service quality is an essential element in the utilization of healthcare services. Evaluating good service quality not only focuses on the physical healing of diseases but also involves the attitude, knowledge, and skills of the staff in providing services. Moreover, effective communication, accurate information, politeness, punctuality, responsiveness, and the availability of adequate facilities and physical environment are equally important. This study employs a descriptive approach with a survey method, examining five dimensions of service quality: reliability, responsiveness, assurance, empathy, and tangible aspects. The population of this study includes all patients who redeem medications and healthcare products at Apotek Armada. Samples were selected using purposive sampling, with the sample size calculated using Cochran's formula, resulting in 385 samples collected in February 2024. The results showed that patient satisfaction levels at Apotek Armada for the reliability dimension were 85.17% (very satisfied), responsiveness 86.97% (very satisfied), assurance 87.39% (very satisfied), empathy 89.27% (very satisfied), and tangible aspects 84.75% (very satisfied). The average satisfaction across all dimensions was 86.71%, categorized as very satisfied. In conclusion, the level of patient satisfaction with pharmaceutical services at Apotek Armada is classified as very high.